Environmental Kuznets curve and energy consumption in Malaysia: A cointegration approach. Issue 9 (1st September 2016) - Saboori, Behnaz; Sulaiman, Jamalludin; Mohd, Saidatulakmal
ABSTRACT: This study examines the long- and short-run relationship between carbon dioxide (CO2 ) emissions, economic growth, energy consumption, foreign trade, and urbanization based on the Environmental Kuznets Curve (EKC) hypothesis in Malaysia for the period 1980–2008. This study employs the Autoregressive Distributed Lag (ARDL) methodology for empirical analysis. The results obtained suggest the existence of three forms of long-run relationships among variables when CO2 emissions, foreign trade, and urbanization are the dependent variables. The long-run results support the EKC hypothesis, which assumes an inverted U-shaped relationship between income and environmental degradation. Moreover, both energy consumption and urbanization are found to have positive effects on CO2 emissions in the long run, while trade has a negative effect on CO2 emissions in both short and long runs. The stability of the variables in the estimated model is also examined. Results suggest that the estimated model is stable over the study period.